Divalent Nickel‐Activated Gallate‐Based Persistent Phosphors in the Short‐Wave Infrared. Issue 4 (27th January 2016) - Liu, Feng; Liang, Yanjie; Chen, Yafei; Pan, Zhengwei
Abstract : Short‐wave infrared (SWIR, 900–1700 nm) persistent phosphors are developed by doping Ni 2+ ions into gallate‐based hosts including zinc gallogermanates, lithium gallates, and lanthanum gallogermanates. These SWIR persistent phosphors exhibit single‐band persistent luminescence in the range of 1000–1600 nm. SWIR persistent luminescence lasting for hours is demonstrated in the Zn3 Ga2 Ge2 O10 :Ni 2+ phosphor.